Preliminary Evidence for the Impact of Combat Experiences on Gray Matter Volume of the Posterior Insula - Clausen, Ashley N.; Billinger, Sandra A.; Sisante, Jason-Flor V.; Suzuki, Hideo; Aupperle, Robin L. (Frontiers in Psychology, 2017)
Background: Combat-exposed veteran populations are at an increased risk for developing cardiovascular disease. The anterior cingulate cortex (ACC) and insula have been implicated in both autonomic arousal to emotional stressors and homeostatic processes, which may contribute to cardiovascular dysfunction in combat veteran populations. The aim of the present study was to explore the intersecting relationships of combat experiences, rostral ACC and posterior insula volume, and cardiovascular health in a sample of combat veterans. Method: Twenty-four male combat veterans completed clinical assessment of combat experiences and posttraumatic stress symptoms. Subjects completed a magnetic reasonance imaging scan and autosegmentaion using FreeSurfer was used to estimate regional grey matter volume (controlling for total grey matter volume) of the rostral ACC and posterior insula. Flow-mediated dilation (FMD) was conducted to assess cardiovascular health. Theil-sen robust regressions and Welch’s analysis of variance were used to examine relationships of combat experiences and PTSD symptomology with 1) FMD and 2) regional grey matter volume. Results: Increased combat experiences, deployment duration, and multiple deployments were related to smaller posterior insula volume. Combat experiences were marginally associated with poorer cardiovascular health. However, cardiovascular health was not related to rostral ACC or posterior insula volume. Conclusion: The present study provides initial evidence for the relationships of combat experiences, deployment duration, and multiple deployments with smaller posterior insula volume. Results may suggest that veterans with increased combat experiences may exhibit more dysfunction regulating the autonomic nervous system, a key function of the posterior insula. However, the relationship between combat and cardiovascular health was not mediated by regional brain volume. Future research is warranted to further clarify the cardiovascular or functional impact of smaller posterior insula volume in combat veterans.